Physico-chemical standardization and nutritional assessment of Devdarvadyarishta - Chinky Goyal; Namrata Joshi; Khem Chand Sharma (Wolters Kluwer Medknow Publications, 2022)
Introduction: Devdarvadyarishta is a honey based anti-diabetic formulation enlisted in Ayurvedic lexicon. Sandhana Kalpana is mentioned under both Ahara and Aushadha Varga, and Asava-arishta were used as food supplements since Vedic period. Devdarvadyarishta was prepared as per conventional method and was subjected to various analytical parameters and nutritional parameters to develop a standard. Methods: Three samples of Devdarvadyarishta were prepared in accordance with Bhaishjya Ratnavali and compared with the market sample on various physico-chemical and phytochemical parameters, high-performance thin-layer chromatography (HPTLC) profiling as well as nutritional value. Results: Respective mean values of prepared samples and market sample were found to be pH - 3.86 and 3.80, specific gravity - 1.0953 and 1.0934, refractive index − 1.41943 and 1.41910, total solid content % w/w − 22.05 and 22.92, reducing sugars 18.18 and 18.50, nonreducing sugars 0.84 and 0.91 and total phenolic content - 0.180% and 0.185%, alkaloids - 0.037% and 0.042%, tannins - 0.11% and 0.10%, saponins − 0.082% and 0.080%, flavonoids - 0.011% and 0.013%, terpenoids − 0.046% and 0.055% and Glycosides - 0.11% and 0.17%. Nutritive value showed mean carbohydrate % of 21.45, fat − 0.21%, protein − 0.07%, and total energy being 86.82 K cal in prepared samples whereas market sample showed 22.97% carbohydrate, 0.25% fat, 0.10% protein, and 88.35 Kcal energy. HPTLC analysis showed two major peaks at Rf 0.87 and 0.90 with Chloroform: methanol solvent system. Conclusion: Physicochemical data for standard of Devdarvadyarishta was set in as a Quality specification for the same. Nutritional value of Devdarvadyarishta, i.e., 86.82 kcal energy supports the ancient views of Sandhana products being used as food adjuncts.